PELATIHAN BRANDING DAN DESAIN PACKAGING UNTUK PRODUK PAKAN TERNAK UMKM MAKMUR DUA PUTRI DESA JATIKALANG KRIAN SIDOARJO - Utomo, Yitno; Yunia Dwie Nurcahyanie; Djoko Adi Walujo; Nushron Ali Mukhtar; Rusdiyantoro (Universitas PGRI Adi Buana Surabaya, 2024)
The implementation of assistance for UMKM Makmur Dua Putri towards business development and professionalism was chosen using Branding and Packaging steps. The branding logo of the letters